Contribution of parental chromosomal abnormalities to recurrent spontaneous abortion: A cytogenetic study on Iraqi couples - Jawad, Rana S. (Iraqi Journal of Cancer and Medical Genetics, 2014)
The main objective of this research study the parental chromosomal abnormalities to recurrent spontaneous abortion Parental chromosomal rearrangements are account for more than 50% of RSA. So, it became necessary in this study to determine whether chromosomal factor is involved in RSA in Iraqi population. Related to that reason, blood samples from couples were collected and chromosomal abnormalities (structural or numerical) were detected by cytogenetic studies. Results from this examination indicated that increased chromosomal abnormalities in couples with advanced age and these abnormalities include translocation and deletion as follows: 46 XY,9qh+ ; 46 XX,21pss ; 46 XY, t(14,15) ; 46XY,14 pstk ; 46 XY ,15 pstk ; 45 XY, 3del. One can expect that, when these abnormalities are transferred to the fetus it can cause disturbance of the chromosomal structure of the fetus which resulted in abortion